A survey on enforcements and practices of human rights policy in Sime Darby Kempas Estate and IOI Group Jasin Lalang Estate / Sharina Sulaiman - Sulaiman, Sharina (Faculty of Plantation and Agrotechnology, 2018)
Malaysia’s oil palm has been a key contributor to the Malaysian economy for decade. The second largest producer of oil palm in the world after Indonesia and being the second exporter of crude palm oil to meet the demand of the world with the opening of new land in Sabah and Sarawak at the end of 2017. The need of human rights policy is to encounter the number of workers from being exploit by their employer. Therefore, it is important that enforcements and practices of human rights is applied at the plantations. The poor implementation of policy would make the workers to be exposed in abuse and exploitation during work and affect the motivation of the semi-skilled worker, unskilled worker and domestic worker to do the job if the policies are not taken seriously. Therefore, this study is conducted to know the factor that can contribute toward the enforcements and practices of human rights policy in the plantation. The data was collected by distributing questionnaire at the Sime Darby Kempas and IOI Group Jasin Lalang at Melaka area. There are three factor that will be observed in this study which are management, workload given and welfare. the questionnaire was distributed to the general worker with total of 63 and 66 respondent respectively from both plantation. from the result, it shows that the factor management of the company give the most contribution to the enforcements and practices of human rights policy in the plantation. Data results also shows that the management are the most dominant factor that contribute to the enforcements and practices of human rights policy in both plantation.